PERUBAHAN KUAT GESER TANAH LEMPUNG TANON PADA METODE ELEKTROOSMOSIS DENGAN VARIASI BEDA POTENSIAL - Tri Nugraheni Handayani; Niken Silmi Surjandari; Noegroho Djarwanti (Prodi Teknik Sipil FT Universitas Sebelas Maret, 2020)
Soft clay soil located in Kalikobok village, Tanon, Sragen is one of soil type that does not qualify to build a structural building on it, because the characters of soft clay soil that has height of water content which is causing the soil carrying capacity becomes low. In other way, if the water content is low, then it will increase the carrying capacity of the soil. Dewatering process is needed, one of the examples is by electroosmosis methods. Electroosmosis is a drainage method by force that drain the water from anode to cathode so it will fix the technical properties of soil. In this study the variables used are the length of time of the electric current and the voltage. The variation of duration is three days and five days, the variation of potential difference that used is 0 volts, 4.5 volts, 9 volts, and 12 volts. The parameters that tested as a comparison are soil shear strength of soil at each voltage and position (anode, middle, cathode). The results showed that the greater application of potential differences can increase the values of c and φ, but the value of c at the cathode position decrease due to water accumulation at the cathode.